An Analysis of dolly red-light district closure impact: 10-year post-transformation study on the psychological and economic vulnerability of susceptible women groups - Setyawan Jefri; Wibowo Joshi Maharani; Indrawardani Ken Fitria (BIO Web of Conferences)
The Dolly area, known as a former red-light district in Surabaya City, is closed, as instructed by local government policy in 2014. This transformation negatively impacted the psychological and economic of vulnerable community groups in the surrounding area, especially women. This research is conducted to revisit the impact of Dolly area closure instruction and policy after ten years. The research is done qualitatively in the Former Dolly red-light district, Surabaya City, by obtaining the primary data through focus group discussions (FGD) in 2023. The analysis method used is TNA (thematic network approach), which is processed and visualized using NVIVO 12 pro. Feminist Standpoint Theory (FST) is used as a theoretical framework to ensure that the knowledge produced involves the participation of individuals who experience it directly. The results show the majority of former sex workers' lives, mainly women, rarely experience a decent life of living after 10 years of Former Dolly red-light district closure. There are three main obstacles (theme) causing this, which is: social, economic and administrative. The poor welfare of this community group leads to discrimination and stigmatization of former Dolly sex workers, and they become more psychologically vulnerable, marginalized and rarely considered as strategic development subjects. Apart from that, excessive social problems such as discrimination and stigmatization affect their economic activity. They lost the freedom to enter a legal sector as labour. Instead, they were forced to enter the shadow economy sectors, such as returning as sexual workers illegally.